Is the current management of status epilepticus in children safe and user friendly? A survey of healthcare professionals. Issue 6 (1st February 2011) - Litherland, C E; Mulla, H
Abstract : Objective: Status epilepticus is a medical emergency with significant morbidity and mortality. Treatment strategies include the use of licensed and unlicensed drugs. A short survey was conducted among specialist staff to establish the current approaches to management, collating staff experiences, and also providing an evaluation of suggested improvements to the current buccal midazolam preparation to improve safety and user friendliness. Method: The survey was in the form of a short structured interview, conducted face to face or over the phone. Ethical approval was not required. Participants were selected from centres from the East of England to Yorkshire. The interviews took place between mid August and end of September 2009. The data were collated anonymously, and analysis was in the form of summary statistics and descriptive analyses. Results: The survey spanned 12 centres (8 tertiary, 4 district general hospital) and associated community staff. 63 professionals were approached, 51 interviews (33 face to face, 18 by telephone) were completed including specialists (8), specialist nurses (12), community paediatricians, (2) pharmacist (10), general paediatricians (2), A&E staff (11) and other staff (6), from specialist schools/clinics/wards. This provided a good cross section of staff experience, and some rich descriptive data around the use of different preparations. Initial analysis shows that buccal midazolam is used solely as first line treatment in 2/12 (17%) centres, but used as an alternative in eight further centres, where lorazepam was used if intravenous access was available. Rectal diazepam was used as a first line alternative in 7/12 (60%) centres. All centres offered buccal midazolam to patients in the community. Two centres restricted the use of midazolam below the age of 1 and 5 years, respectively, choosing rectal diazepam instead. Standard doses were given in 2/10 (20%) of the centres, based on BNFC banding, rather than individualised doses based on weight. A major theme was the importance of staff providing wide education to families, carers and professionals on dosing and administration criteria, to ensure safe and effective treatment in a timely way. Knowledge of the license status of preparations was variable. Multi-dose formulations of buccal midazolam were used by all and the most popular improvement suggested for this drug was a prefilled single dose syringe, closely followed by a licensed formulation and enabling paramedics to administer it. Conclusion: There appears to be wide acceptance of the buccal midazolam preparation as a safe and effective treatment for status epilepticus despite it not being licensed. The development of a prefilled, single dose syringe was regarded as a positive improvement, having benefits for both the user and patient, ensuring that the correct dose is given and that treatment is administered quickly. This should not diminish however, the wide education required for families, carers and the multidisciplinary team. The survey was funded by Therakind Ltd.